Pemanfaatan Microsoft Excel Sebagai Sarana Pembelajaran Digital Dalam Meningkatkan Pemahaman Pengolahan Data - Fiko Mahmudin Ais; Sobur Cakra Diningrat; Azrial Firmansyah; Yudistira Tanjung; Hendi Anandika Yanuar Rahman; Gregorius Pendianus Halawa; Yogi Priatama; Rusdiyanto; Muhammad Jidan Ramdani; Luthfi Muhammad Fakhri; Santi Rahayu (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology requires the education sector to adapt by implementing digital-based learning methods. Microsoft Excel is a powerful data processing software with great potential as a learning tool. However, at SMKS Yadika 10 Kosambi, its utilization has not been optimal, leading many students to struggle with understanding data processing concepts. Through this Community Service Program (PKM), training on the use of Microsoft Excel was provided to Grade X students to improve their digital literacy and data processing skills. The training was conducted interactively, covering topics such as introduction to Excel, basic formulas, and creating charts. The results showed an improvement in students’ understanding of data processing concepts and their ability to use basic Excel features, which are expected to support their readiness for the technology-driven job market.